Extramatrical Mycelium and Ectomycorrhizal Community Composition of Quercus pubescens in a Sub-Mediterranean Stress-Prone Environment - Mrak, Tanja; Šibanc, Nataša; Brailey-Jones, Philip; Štraus, Ines; Gričar, Jožica; Kraigher, Hojka (Frontiers in Forests and Global Change, 2021)
Temporal studies that would offer insight into resilience of ectomycorrhizal (ECM) communities in stress prone climates are scarce despite their role in tree nutrition and water supply. Our study characterized the vitality, community composition, diversity, and function of Quercus pubescens Willd. ECM fungi in the Sub-Mediterranean stress-prone environment for two consecutive years (June 2016-May 2018) and related the investigated measures to environmental parameters. ECM community was assessed for species actively associating with root tips and exploring the soil volume through the assessment of mycelial ingrowth into sand-filled mesh bags. The investigated period was characterized by a drier than average summer combined with wildfire in 2016 followed by another dry summer in 2017. The vital to non-vital ECM root tip ratio decreased below one in August 2016 and remained low until January 2018. This was ascribed to a series of stress events that occurred at the site including sequential droughts and wildfire. The most abundant ECM lineages on root tips were Tomentella and other Thelephoraceae, Sebacina and Cenococcum while in mesh bags the most abundant were Tomentella, Sebacina, Pseudotomentella, Pyronemataceae, Inocybe, Cortinarius, Agaricales and Boletales lineages. High intra-site variability was observed, with ECM communities directly associated with root tips and exploring the soil volume varying significantly among the plots. Community composition was stable over time, while species richness varied with mean air and soil temperature, relative air humidity, and solar radiation. The most abundant exploration type observed at this site was short distance, which was associated with precipitation along with long distance exploration type. The medium distance exploration type was temporally variable and responded to soil temperature and relative air humidity reflecting seasonality at the site. The presented results indicate complex relationships between environmental parameters, abiotic stress, and ECM fungi.